Analysis of the correlation between serum anti-PLA2R antibodies and thromboembolic events in patients with idiopathic membranous nephropathy - Sun Miao-xin; Wang Ding-ding; Wu Hao-wen; Cai Pan-pan; Xin Ye; Zhao Xin-cheng; Chai Wen-xiu; Li Yun-xia; Li Zi-wei; Duan Li-ping (Linchuang shenzangbing zazhi, 2025)
ObjectiveTo investigate the correlation between serum anti-phospholipase A2 receptor antibodies （a-PLA2R Ab） level and thromboembolic events in patients with idiopathic membranous nephropathy （IMN）.MethodsA total of 279 patients diagnosed with IMN in Handan Central Hospital from January 1， 2020 to May 31， 2022 were included. Based on serum a-PLA2R Ab levels， IMN patients were divided into positive （serum a-PLA2R Ab≥14 RU/mL） and negative groups， and clinical data differences were compared. Receiver operating characteristic （ROC） curves were utilized to determine the optimal cutoff value of serum a-PLA2R Ab titer in distinguishing thromboembolic events.ResultsOf the 279 patients， 181 （64.9%） were male， with a male-to-female ratio of 1.85∶1. Their average age was （52.41±13.54）years. A total of 215 （77.1%） patients were a-PLA2R Ab positive and 64 （22.9%） were negative. Twenty-seven （9.7%） patients experienced venous thrombotic events. The proportions of male patients （68.4% vs 53.1%）， the 24-hour urine total protein quantification ［24 h UTP， 5.69 （3.91， 8.27） g vs 4.46 （1.98， 5.96） g］， serum creatinine ［SCr， （75.22±24.32） mmol/L vs （67.27±30.71） mmol/L］， total cholesterol ［TCH， （7.70±2.35） mmol/L vs （7.02±1.83） mmol/L］， low-density lipoprotein ［LDL， （4.55±1.53） mmol/L vs （4.08±1.25） mmol/L］， lipoprotein a ［Lipo a， （0.060±0.043） mg/L vs （0.045±0.033） mg/L］， apolipoprotein B ［Apo B （1.48±0.48） g/L vs （1.31±0.40） g/L］， fibrinogen ［Fib， 4.84 （3.98， 5.77） g/L vs 4.04 （3.49， 5.02） g/L］， D-dimer ［（1.87±2.37） mg/L vs （0.96±1.07） mg/L］， and fibrinogen/albumin ratio ［FAR， 0.199 （0.150， 0.260） vs 0.142 （0.110， 0.180）］ were all significantly higher in the a-PLA2R Ab positive group than those in the a-PLA2R Ab negative group （all P<0.05）. While serum albumin ［Alb， （24.51±5.26） g/L vs （28.74±6.22） g/L］ and estimated glomerular filtration rate ［eGFR， （94.50±21.60） mL·min‒1·（1.73 m2）‒1 vs （103.00±20.28） mL·min‒1·（1.73 m2）‒1］ were significantly lower than those in the a-PLA2R Ab negative group （all P<0.05）. Although the incidence of thromboembolic events in the a-PLA2R Ab positive group was higher than that in the a-PLA2R Ab negative group， the difference was not statistically significant （P=0.195）. The ROC curve suggested an optimal cutoff value of 142.535 RU/mL for predicting thromboembolic events， with a sensitivity of 63.2%， a specificity of 69.4%， and an area under the curve （AUC） of 0.663 （95%CI： 0.554-0.771）， and the highest Youden index of 0.324. Univariate and multivariate logistic regression analyses showed that venous thromboembolic events were positively correlated with D-dimer （OR=1.402， P<0.001） and negatively correlated with activated partial thromboplastin time （APTT） （OR=0.821， P=0.044）. The risk of venous thromboembolic events was also positively associated with a-PLA2R Ab>142.535 RU/mL （OR=3.466， P=0.007）.ConclusionSerum Alb and eGFR are lower in the a-PLA2R Ab positive group， while the 24-hour UTP， TCH， D-Dimer and other indicators are higher. The ROC curve indicated that the best cutoff value for predicting thromboembolic events was 142.535 RU/mL. The level of a-PLA2R antibodies greater than 142.535 RU/mL and D-Dimer are positively correlated with venous thromboembolism events in patients with IMN， while APTT is negatively correlated.